2017
DOI: 10.1002/2017ja024548
|View full text |Cite
|
Sign up to set email alerts
|

On the Dawn‐Dusk Asymmetry of the Kelvin‐Helmholtz Instability Between 2007 and 2013

Abstract: Using data from Time History of Events and Macroscale Interactions during Substorms (THEMIS), a statistical study was performed to determine whether a dawn‐dusk asymmetry exists in the occurrence rates of the Kelvin‐Helmholtz instability during Parker‐Spiral (PS) and Ortho‐Parker‐Spiral (OPS) orientations of the interplanetary magnetic field (IMF). It is determined from the data that there is a strong preference toward the dawnside during PS orientation, and although a preference to the duskside during OPS is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 60 publications
2
42
0
Order By: Relevance
“…A revisit of a statistical survey of 7 years of THEMIS data (Kavosi and Raeder 2015), taking this aspect into account, tends to confirm this prediction observationally (Henry et al 2017). The normalized occurrence rates showed clear dawn flank preference during PS IMF, and dusk flank preference during northward IMF (Henry et al 2017).…”
Section: Multi-spacecraft Visionmentioning
confidence: 83%
“…A revisit of a statistical survey of 7 years of THEMIS data (Kavosi and Raeder 2015), taking this aspect into account, tends to confirm this prediction observationally (Henry et al 2017). The normalized occurrence rates showed clear dawn flank preference during PS IMF, and dusk flank preference during northward IMF (Henry et al 2017).…”
Section: Multi-spacecraft Visionmentioning
confidence: 83%
“…The asymmetric plasma mass density distribution is also the cause of the lower eigenfrequencies in the afternoon sector. However, Henry et al () found that the KHI was statistically more common on the dawnside which could also account for this asymmetry. However, our discussion in the following sections establishes that both the KHI and pressure pulse mechanism could be drivers of the fundamental eigenmode.…”
Section: Discussionmentioning
confidence: 98%
“…It is found that the wind becomes collimated toward the rotation axis of the Sun (or the star) by the magnetic pinching of the spiral or twisted field. In fact, any stationary, axisymmetric magnetized wind collimates toward the rotation axis at large distances (Heyvaerts and Norman, 1989). It is useful to introduce the poloidal-toroidal expression of the magnetic field in the two-dimensional MHD treatment:…”
Section: One-dimensional Treatmentmentioning
confidence: 99%
“…Of course, irregular or transient phenomena (such as coronal mass ejections or co-rotating interaction regions) cause local, large-amplitude deviations from the mean field. Recent study by Henry et al (2017) indicates that the IMF (at the Earth orbit) can be regarded as the Parker spiral type when the IMF is sufficiently inclined to the Earth orbital plane, either (1) B x > 0.4B and B y < −0.4B or (2) B x < −0.4B and B y > 0.4B, where B x is the sunward component of the magnetic field (GSE-X direction), B y is the dawn-to-dusk component of the field (GSE-Y direction), and B is the magnetic field magnitude. The IMF can be more radial and of the ortho-Parker spiral type (valid under |B x | > 0.4B t , where B t denotes the transverse component of the magnetic field to the radial direction from the Sun, B t = B 2 y + B 2 z ) or oriented more northward or southward |B z | > 0.5B t .…”
Section: Introductionmentioning
confidence: 99%